2019
DOI: 10.36366/frontiers.v31i2.457
|View full text |Cite
|
Sign up to set email alerts
|

Developing Global Competencies through International Teaching: Using Critical Cosmopolitan Theory to Compare Case Studies of Two Study Abroad Programs

Abstract: For students to become global citizens they need globally competent teachers. The purpose of this article is to describe and compare the development of global competencies in teacher candidates who participated in international teaching-focused study abroad programs. The article is framed by Critical Cosmopolitan Theory (Byker, 2013), which offers a lens for the development of global competencies through the fusion of critical consciousness (Freire, 1970) and cosmopolitanism (Appiah, 2010). In the field of tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In order, the summary covers findings about Black students' destination interests, their learning activities and experiences while abroad, their learning outcomes, and elements of study abroad program design positive to them. 42 Black students were not only attracted to heritage destinations and locations (Blake et al, 2020;Bush et al, 2022) but also to other destinations, e.g., Central America (Dietz et al, 2011;Smith-Augustine et al, 2014), South and North Europe (Willis, 2015), Africa (Byker & Xu, 2019;Willis, 2015), and East Asia (Byker & Xu, 2019;Lu et al, 2015). Across these destinations, the students engaged in their study abroad experiences through various activities, including site visits, local encounters, community service, storytelling, group discussions and, most importantly, regular journaling and written (self-)reflection (Blake et al, 2020;Edwards, 2020;Smith-Augustine et al, 2014).…”
Section: Summary Of Research Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order, the summary covers findings about Black students' destination interests, their learning activities and experiences while abroad, their learning outcomes, and elements of study abroad program design positive to them. 42 Black students were not only attracted to heritage destinations and locations (Blake et al, 2020;Bush et al, 2022) but also to other destinations, e.g., Central America (Dietz et al, 2011;Smith-Augustine et al, 2014), South and North Europe (Willis, 2015), Africa (Byker & Xu, 2019;Willis, 2015), and East Asia (Byker & Xu, 2019;Lu et al, 2015). Across these destinations, the students engaged in their study abroad experiences through various activities, including site visits, local encounters, community service, storytelling, group discussions and, most importantly, regular journaling and written (self-)reflection (Blake et al, 2020;Edwards, 2020;Smith-Augustine et al, 2014).…”
Section: Summary Of Research Findingsmentioning
confidence: 99%
“…Although research has shown one of these barriers to be resistance from family, practitioners can flip the script by acknowledging the value Black students place on their family relationships via engaging with families during program outreach. Peers also serve as a valuable resource; for example, those who return from a study abroad experience are often interested in promoting study abroad to their friends, family, and acquaintances back home (Byker et al, 2019;White et al, 2011). Focusing on what Black students uniquely have to 44 gain can also help to center the Black student in discussions about the value of study abroad, which may look different than the benefits for the traditional White student.…”
Section: Shift Away From a Deficiency Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, global teachers are, at the same time, global educators and global learners (Byker & Xu, 2019; Carano, 2013; Little et al, 2019) since it is necessary to support the development of their attitudes toward global learning during teacher education programs (Bamber et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Byker (2019) found that development of global competencies and sense of global citizenship were connected to PSTs' social and emotional learning while abroad. Additionally, study abroad influences PSTs' identity as a global citizen and their concerns about global issues (Byker 2016;Byker & Xu, 2019;Dunn et al, 2014). These research studies around PSTs areas of growth related to being a globally competent teacher highlight the pedagogical value of study abroad for teacher education.…”
Section: Internationalizing the Curriculummentioning
confidence: 99%